Trajectories of memory, language, and visuoperceptual problems in people with stroke during the first year and controls in Colombia. Issue 3 (30th January 2021) - Olabarrieta-Landa, Laiene; Pugh, Mickeal; Calderón Chagualá, Amilkar; Perrin, Paul B.; Arango-Lasprilla, Juan Carlos
Abstract: Aim: Neuropsychological normative data for Latin America have been recently published, and for Colombia, in particular, but longitudinal neuropsychological outcomes after stroke have not yet been examined in this global region. The purpose of the current study was to compare functioning of individuals with stroke in Colombia, South America during the first year post-stroke to healthy controls across neuropsychological assessments of memory, language, and visuoperceptual impairments. Method: A sample of 50 individuals with stroke (mean age = 51.58) and 50 matched healthy controls (mean age = 51.54) from Colombia were included in this study. Because of a lack of access to health services, individuals with stroke did not receive any inpatient or outpatient cognitive or behavioral rehabilitation. Participants were assessed on 10 visuoperceptual, language, and memory tasks at 3, 6, and 12  months. Results: Trajectories of neuropsychological performance were significantly worse among individuals with stroke than healthy controls across every index. Further, hierarchical linear models suggested that although both individuals with stroke and controls generally improved over time on these assessments, the improvements among individuals with stroke were often of no greater magnitude than the improvements seen in controls, suggesting extremely low levels of rehabilitation gains in Colombia. Only three of the 10 neuropsychological assessments did a significant time*group interaction occur, suggesting greater gains for the stroke group than controls. Conclusion: These findings suggest profound disparities in post-stroke cognitive functioning in Colombia compared to other more developed global region and underscore the importance of comprehensive cognitive rehabilitation services for individuals with stroke in Colombia and other similar global regions. Implications for rehabilitation: Because this study found only negligible cognitive improvements beyond practice effects over the first year after stroke in Colombia among individuals without access to acute rehabilitation, it is imperative that comprehensive cognitive rehabilitation services be implemented immediately during the acute rehabilitation period. Memory, language, and visuoperceptual training strategies can be implemented for people with stroke in underserved global regions as part of the standard of care for stroke rehabilitation. Cognitive rehabilitation strategies should be adapted into Spanish and pilot tested in Latin America to ensure cultural equivalence. Culturally competent cognitive rehabilitation strategies should be tailored based on varied educational and literacy levels.